INTEGRATED REPORTING: A REVIEW ARTICLE - Hayder Mahdi Allawi (Scholar Express Journals, 2025)
Most studies have shown the great importance of integrated reports, especially after the occurrence of many financial crises for a number of major companies in the world, which emphasized the importance of disclosing nonfinancial information and events in addition to financial events and information due to the shortcomings of traditional financial reports and their failure to provide sufficient information about non-financial performance. Integrated reports provide users with the financial information and nonfinancial information they need with economic, environmental and social dimensions that enable them to obtain a clear picture of the current and future performance of institutions. Therefore, the research aimed to identify the concept of integrated reports, know the importance and objectives of these reports, identify their informational content and the challenges facing their implementation.
Keywords: Integrated reporting; traditional reports